Intensification of biotransformations using deep eutectic solvents: Overview and outlook. (March 2018) - Juneidi, Ibrahim; Hayyan, Maan; Hashim, Mohd Ali
Graphical abstract: Highlights: Deep eutectic solvents (DESs) have received increased attention recently. DESs have played a pivotal role in diverse biochemical processes. Among these, biotransformations using DESs have been explored recently. This review article aims to shed light on this promising research area. New routes of biotransformations are possible using these neoteric solvents. Abstract: As the interest in green chemistry increases, developing new and more efficient solvents has been put into focus. Deep eutectic solvents (DESs) composed mostly of organic salts with negligible vapor pressure and non/low flammability are proposed as replacements for volatile solvents. Although the potential applications of DESs in diverse fields are unquestionable, their physicochemical properties and biological characteristics are yet to be fully explored. In addition, understanding their environmental impact at different trophic levels is the main step toward designing environmentally benign DESs. The use of DESs in biotransformations, including enzymatic and whole-cell, has gathered increasing interest. DESs enhance the activity and stability of several enzymes such as lipase, protease, and cellulase. Thus, this review aims to provide a presentation about the status of biological interactions of DESs and their application in the field of biotransformation.